2012
DOI: 10.3892/mmr.2012.1212
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association between CYP1A1 T6235C polymorphism and coronary artery disease: Evidence from a meta-analysis

Abstract: A number of studies have evaluated the correlation between the cytochrome P450 1A1 (CYP1A1) T6235C polymorphism and coronary artery disease (CAD) risk, however, at present the results remain inconclusive. To provide a more robust investigation of this correlation, a meta-analysis was performed. In the present study, a systematic search of PubMed, Embase and CBM databases for studies published prior to June 6, 2012 was performed. The correlation between the CYP1A1 T6235C polymorphism and CAD risk was assessed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
(62 reference statements)
0
1
0
Order By: Relevance
“…Taspinar et al [23] also suggested that CYP1A1 genotypes were not significantly different between patients and controls. A meta- analysis [24] suggested that the CYP1A1 rs4646903 polymorphism was not correlated with CAD risk. Yeh et al [25] suggested that CYP1A1 polymorphism may be associated with the lower susceptibility to CAD, particularly in non-smokers.…”
Section: Discussionmentioning
confidence: 99%
“…Taspinar et al [23] also suggested that CYP1A1 genotypes were not significantly different between patients and controls. A meta- analysis [24] suggested that the CYP1A1 rs4646903 polymorphism was not correlated with CAD risk. Yeh et al [25] suggested that CYP1A1 polymorphism may be associated with the lower susceptibility to CAD, particularly in non-smokers.…”
Section: Discussionmentioning
confidence: 99%